Investigating the Behavioral Adoption Intention of Mobile Government Services From the Value-Based Adoption Model Perspective - Isaac Kofi Mensah; Deborah Simon Mwakapesa (IEEE Access)
This research investigated the determinants affecting the adoption of m-government services through the framework of the Value-Based Adoption Model. This study bridges the gap in the literature in two aspects: first relating to the moderating influence of mobility and security respectively on the relationship between benefits (usefulness and enjoyment) and perceived value of m-government services. Second the moderating effect of mobility and security respectively on the interaction between perceived value and the adoption intention of m-government services. The analysis utilizing a dataset comprising 467 Chinese citizens was processed with Smart Partial Least Squares software, employing structural equation modeling techniques. The findings indicate that perceived usefulness, enjoyment, technical aspects, and perceived costs directly influence the perceived value of m-government services. Furthermore, the perceived value associated with m-government was identified as influencing the adoption behavior of m-government services. The moderation analysis showed that mobility played a significant role in influencing the relationship between the benefits of usefulness and enjoyment and the perceived value of m-government services. Moreover, mobility was a key factor in moderating the influence of perceived value on the adoption of m-government services. In addition, security played a crucial role in influencing the relationship between enjoyment and the perceived value of m-government. It also had a significant moderating effect on the relationship between perceived value and the intention to adopt m-government services. Also, the findings of the study revealed that security does not play a significant moderating role in the effect of usefulness on the perceived value of m-government services. These results provide insights into the implications of these findings for the development of value-oriented m-government services.